2023
DOI: 10.1097/prs.0000000000010318
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Breast Reconstruction in Massive Weight Loss Patients: Understanding Risks in a Growing Population

Abstract: strong correlation exists between obesity and breast cancer risk. 1 Obesity has also been shown to increase complications in abdominally based autologous breast reconstruction, leading to a denial of procedures for patients with obesity. 2,3 This concern for increased complications in patients with obesity may prompt clinicians to suggest bariatric surgery as a strategy to help these patients achieve weight loss in anticipation of breast reconstruction. 2,4 Given this Background: Massive weight loss (MWL) may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…These conclusions were based on a cohort of 916 patients undergoing 1465 flaps, of which 39 patients had a history of massive weight loss [17]. Notably, this study also found that despite the increased risk of complications and increased need for surgical revisions, BREAST-Q scores were not statistically different between massive weight loss patients and patients without a history of weight loss with respect to satisfaction with breasts or satisfaction with the surgeon [17].…”
Section: Massive Weight Lossmentioning
confidence: 65%
See 2 more Smart Citations
“…These conclusions were based on a cohort of 916 patients undergoing 1465 flaps, of which 39 patients had a history of massive weight loss [17]. Notably, this study also found that despite the increased risk of complications and increased need for surgical revisions, BREAST-Q scores were not statistically different between massive weight loss patients and patients without a history of weight loss with respect to satisfaction with breasts or satisfaction with the surgeon [17].…”
Section: Massive Weight Lossmentioning
confidence: 65%
“…Our institution investigated outcomes of autologous breast reconstruction on patients with a history of massive weight loss, ultimately concluding that autologous breast reconstruction can be successfully undertaken in this population but may have a higher incidence of postoperative complications including delayed wound healing, surgical site infections, and partial flap losses as well as an increased need for donor and flap site revisions [17]. These conclusions were based on a cohort of 916 patients undergoing 1465 flaps, of which 39 patients had a history of massive weight loss [17].…”
Section: Massive Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation